Exploring How Low Oxygen Post Conditioning Improves Stroke-Induced Cognitive Impairment: A Consideration of Amyloid-Beta Loading and Other Mechanisms - Zhao, Zidan; Hood, Rebecca J.; Ong, Lin Kooi; Pietrogrande, Giovanni; Sanchez Bezanilla, Sonia; Warren, Kirby E.; Ilicic, Marina; Kluge, Murielle G.; TeBay, Clifford; Ottersen, Ole P.; Johnson, Sarah J.; Nilsson, Michael; et al. (Frontiers in Neurology, 2021)
Cognitive impairment is a common and disruptive outcome for stroke survivors, which is recognized to be notoriously difficult to treat. Previously, we have shown that low oxygen post-conditioning (LOPC) improves motor function and limits secondary neuronal loss in the thalamus after experimental stroke. There is also emerging evidence that LOPC may improve cognitive function post-stroke. In the current study we aimed to explore how exposure to LOPC may improve cognition post-stroke. Experimental stroke was induced using photothrombotic occlusion in adult, male C57BL/6 mice. At 72 h post-stroke animals were randomly assigned to either normal atmospheric air or to one of two low oxygen (11% O2) exposure groups (either 8 or 24 h/day for 14 days). Cognition was assessed during the treatment phase using a touchscreen based paired-associate learning assessment. At the end of treatment (17 days post-stroke) mice were euthanized and tissue was collected for subsequent histology and biochemical analysis. LOPC (both 8 and 24 h) enhanced learning and memory in the 2nd week post-stroke when compared with stroke animals exposed to atmospheric air. Additionally we observed LOPC was associated with lower levels of neuronal loss, the restoration of several vascular deficits, as well as a reduction in the severity of the amyloid-beta (Aβ) burden. These findings provide further insight into the pro-cognitive benefits of LOPC.